Evidence-Based Medicine and the Potential for Inclusion of Non-Biomedical Health Systems: The Case for Taijiquan - Langweiler, Mark J. (Frontiers in Sociology, 2021)
Many traditional and complementary and alternative healthcare systems or practices, such as Traditional Chinese Medicine, taijiquan, or acupuncture, are easily found in many North American and European cities. For the most part these practices are not accredited, and their validation remains limited. This is primarily the result of the lack of modern scientific research. Additionally, the studies that are performed rely on evidence and research designs that often negate the true features of these practices with a loss of authenticity. Is it possible or even desirable for these systems to acquire accreditation and inclusion? If so, given the apparent, subjective nature of these practices, can a pluralistic approach to healthcare that retains the Western values of science and medicine be developed that yet respects the diversity of different concepts about life, health and services while permitting these practices to maintain their authenticity? And is it possible to develop a regulatory framework that practitioners can use? The current paper examines questions concerning the uses of non-Western healthcare practices without the loss of their authentic nature. The process of integration is here examined using the inclusion of taijiquan as a health-promoting martial art as the model.